Stratified Analysis of Factors Associated With Mortality in Patients With COVID-19 Based on Cancer and Diabetes - Ya-Chun, Liao; Hsin-Hua, Chen; Po-Yu, Liu; Zhi-Yuan, Shi; Yu-Hui, Lin; Che-An, Tsai; Yung-Chun, Chen; Chien-Hao, Tseng; Chia-Wei, Liu; Tzu-Hua, Wu; Ming-Ju, Wu; Shih-Ping, Lin (International Journal of Global Health, 2024)
Background Cancer and diabetes are risk factors for COVID-19 mortality rates. Remdesivir, dexamethasone, and vaccines are used to improve clinical outcomes. We aimed to evaluate the factors associated with COVID-19 mortality rates. Methods This retrospective study enrolled moderate to critical COVID-19 patients. The index day was the day of the COVID-19 diagnosis. Patients were followed up until either death or discharge. A two-way analysis of variance examined the interaction between independent mortality risk factors. Results A total of 205 patients were analyzed, and the mortality rate was 29.5% (n=60/205). The cumulative survival rate was significantly lower in patients with a CCI score ≥ 6, cancer, and diabetes. In multivariate analysis, critical illness, cancer, diabetes, chronic liver disease, a CCI score ≥ 6, unvaccinated, and early use of remdesivir/dexamethasone were independent risk factors for mortality. The onset of remdesivir/dexamethasone ≥ 2 days and < 3 doses of vaccinations were higher mortality rate, with its impact being more significant amongst patients with cancer/diabetes, compared to those without cancer/diabetes (p for interaction = 0.046/0.049, 0.060/0.042, and 0.038/0.048 respectively). Conclusions COVID-19 vaccination ≥ 3 doses and early administration of remdesivir and dexamethasone can significantly reduce mortality rates, particularly in patients with cancer or diabetes.
Keywords: Cancer; COVID-19; COVID-19 vaccine; Diabetes; Mortality